Biomechanical comparison of all-on-4 and all-on-5 implant-supported prostheses with alteration of anterior-posterior spread: a three-dimensional finite element analysis - Sun, Xin; Cheng, Kangjie; Liu, Yunfeng; Ke, Sipeng; Zhang, Wentao; Wang, Linhong; Yang, Fan (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The all-on-4 concept is widely used in clinical practice. However, the biomechanical changes following the alteration of anterior-posterior (AP) spread in all-on-4 implant-supported prostheses have not been extensively studied. Methods: Three-dimensional finite element analysis was used to compare the biomechanical behavior of all-on-4 and all-on-5 implant-supported prostheses with a change in anterior-posterior (AP) spread. A three-dimensional finite element analysis was performed on a geometrical mandible model containing 4 or 5 implants. Four different implant configurations were modeled by varying the angle of inclination of the distal implants (0°and 30°), including all-on-4a, all-on-4b, all-on-5a, and all-on-5b, and a 100 N force was successively applied to the anterior and unilateral posterior teeth to observe and analyze the differences in the biomechanical behavior of each model under the static influence at different position. Results: Adding an anterior implant to the dental arch according to the all-on-4 concept with a distal 30° tilt angle implant exhibited the best biomechanical behavior. However, when the distal implant was implanted axially, there was no significant difference between the all-on-4 and all-on-5 groups. Discussion: In the all-on-5 group, increasing the AP spread with tilted terminal implants showed better biomechanical behavior. It can be concluded that placing an additional implant in the midline of the atrophic edentulous mandible and increasing the AP spread might be beneficial in improving the biomechanical behavior of tilted distal implants.